Effect of position on gross motor function and spasticity in spastic cerebral palsy children - Wardah Rauf; Samia Sarmad; Iqra Khan; Muhammad Jawad (Journal of the Pakistan Medical Association, 2021)
Objective: To evaluate the effect of positioning on gross motor function and spasticity in spastic quadriplegic cerebral palsy children with Gross Motor Function Classification System level IV and V. Methods: A quasi-experimental study was conducted at two Paediatric Physical Therapy Centres from November 2018 to July 2019. The study was comprised of seventy four children with quadriplegic cerebral palsy aged between 3 to 8 years. Data was obtained and gross motor functional abilities and spasticity were assessed by GMFM-88 and Modified Ashworth Scale respectively. Twenty four-hour positioning in specific seats, night positioning and standing frames for six months. The child was being positioned in 24 hours according to his challenges for the period of six months. Semi reclined positioning was performed to manage aspiration, oral leak and to develop retention. Prone positioning was done to develop righting reactions, functional sitting position was used in the treatment regime to attain better upright position and neutral pelvic standing using standing frames. SPSS 24 was used to analyse the data. Results: Paired t-test reported significant improvement in the test scores in lying position, rolling, sitting position, crawling, kneeling, standing, walking or running. n=59 subjects exhibited improvement in the spasticity before and after interventional procedures, while n=15 showed no improvement as the value of p<0.05. Conclusion: Twenty-Four-hour proper body positioning and postural techniques improved gross motor functioning in all of the five dimensions of functioning. The overall spasticity in quadriplegic cerebral palsy children was also reduced due to appropriate positioning techniques. Continuous....